Robert Bárány, a scientist with many interests - Péricles Maranhão-Filho; Anders Bárány (Arquivos de Neuro-Psiquiatria)
ABSTRACT Austrian-born Robert Bárány was a scientist with many interests. This article highlights some of these interests and also some personal traits. He enrolled as a surgeon in World War I, was captured by the Russians in 1915 and, while still in the prison camp, was awarded the 1914 Nobel Prize in Physiology or Medicine for his work in otology. In 1916, he accepted an offer from Uppsala University, Sweden, and worked there for almost 20 years. He died shortly before his 60th birthday, in 1936.